IMPLEMENTATION MODEL FOR CALCULATING TOTAL INVENTORIES MATHEMATICAL COTTON ON THE OPTIMAL PT. XYZ USING MICROSOFT VISUAL BASIC 6.0 - Suyanti Suyanti; Sahni Damerianta, SKom, MMSI Sahni Damerianta, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Determine the model is a necessity in a company, the amount of raw material cotton uncertain within a company can result in losses, the amount of inventory that are too much than the required amount will result in overlapping inventories and working capital investment means embedded and useless. In addition cotton is easy once the goods are damaged and if damaged can not be used again in other words should be discarded. We recommend that if the total inventory is not sufficient number of requests or needs will lead to cessation of the production process that can damage the company image in the eyes of the customer.Therefore we need a model able to address the conditions of supply of, nor in determining the optimal model of cotton supply in the PT. XYZ, where the use of cotton each month is uncertain. The mathematical model is an approach that the authors analyzed for application at. XYZ. With this mathematical model it can be determined the optimal amount of cotton supplies each month is also equipped with a table-making opportunity loss as consideration for making the decision.